2014
DOI: 10.1681/asn.2013050545
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Antioxidant Therapy in Hemodialysis (PATH)

Abstract: Increased markers of oxidative stress and acute-phase inflammation are prevalent in patients undergoing maintenance hemodialysis therapy (MHD), and are associated with increased mortality and hospitalization rates and decreased erythropoietin responsiveness. No adequately powered studies have examined the efficacy of antioxidant therapies on markers of inflammation and oxidative stress. We tested the hypothesis that oral antioxidant therapy over 6 months would decrease selected biomarkers of acute-phase inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 57 publications
5
49
0
Order By: Relevance
“…101 Whether the oxidative stress of uremia is a primary driver of CVD or a secondary phenomenon is unclear. Small randomized trials in ESRD patients have not shown any significant benefit of antioxidant treatment, 102 suggesting that oxidative stress may not be a primary mediator of cardiovascular risk. Alternatively, targets and interventions that are more specific for uremia related oxidative stress should be studied.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…101 Whether the oxidative stress of uremia is a primary driver of CVD or a secondary phenomenon is unclear. Small randomized trials in ESRD patients have not shown any significant benefit of antioxidant treatment, 102 suggesting that oxidative stress may not be a primary mediator of cardiovascular risk. Alternatively, targets and interventions that are more specific for uremia related oxidative stress should be studied.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…When administered to CKD patients, LA improved some biomarkers, but not the oxidative stress biomarkers. [7][8][9]11,12 This lack of antioxidant effect of LA may be due to the fact that the tested groups were in the later stages of CKD, a condition where uremia is maximal. If uremic toxins have indeed a role in Nrf2 inactivation, LA supplementation should be started before the installation of uremia.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies showed that oral administration of LA, particularly to hemodialysis (HD) patients for several weeks, led to an improvement in asymmetric dimethylarginine (ADMA) 7 and C-reactive protein 8 levels, or erythropoietin resistance index, 9 oxidative stress biomarkers levels were not altered in the LA-treated groups of CKD 10 or HD patients. 8,9,11,12 In experimental CKD, intraperitoneally-injected LA for 8 weeks has been shown to improve blood pressure, renal function, and oxidative markers after 5/6 nephrectomy in rats, 13 while oral LA for 8 weeks decreased blood pressure, as well as vascular injury 14 when compared with the non-treated nephrectomized rats. In acetaminophen-induced uremia, orally-fed LA for 15 days prevented an increase in plasma urea, creatinine, and malondialdehyde levels in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have suggested that increased oxidative stress is highly prevalent in patients receiving dialysis, contributing to the increased incidence of the adverse outcomes [4]. Two previous randomized, placebo-controlled trials of patients undergoing hemodialysis have shown positive effects of antioxidant therapy on the development of ASCVDs [5,6], despite a number of unsuccessful clinical trials using a range of interventions aimed to improve the prognosis in this population [4,7].…”
Section: Introductionmentioning
confidence: 99%